High Prevalence of Gut Microbiota Colonization with Broad-Spectrum Cephalosporin Resistant Enterobacteriaceae in a Tunisian Intensive Care Unit - Maamar, Elaa; Ferjani, Sana; Jendoubi, Ali; Hammami, Samia; Hamzaoui, Zaineb; Mayonnove-Coulange, Laure; Saidani, Mabrouka; Kammoun, Aouatef; Rehaiem, Amel; Ghedira, Salma; Houissa, Mohamed; Boutiba-Ben Boubaker, Ilhem; et al. (Frontiers in Microbiology, 2016)
Healthcare-associated infections due to cefotaxime-resistant (CTX-R) Enterobacteriaceae have become a major public health threat, especially in intensive care units (ICUs). Often acquired nosocomially, CTX-R Enterobacteriaceae can be introduced initially by patients at admission. This study aimed to determine the prevalence and genetic characteristics of CTX-R Enterobacteriaceae-intestinal carriage in ICU patients, to evaluate the rate of acquisition of these organisms during hospitalization, and to explore some of the associated risk factors for both carriage and acquisition. Between December 2014 and February 2015, the 63 patients admitted in the ICU of Charles Nicolle hospital were screened for rectal CTX-R Enterobacteriaceae colonization at admission and once weekly thereafter to identify acquisition. CTX-R Enterobacteriaceae fecal carriage rate was 20.63% (13/63) at admission. Among the 50 non-carriers, 35 were resampled during their hospitalization and the acquisition rate was 42.85% (15/35). Overall, 35 CTX-R Enterobacteriaceae isolates were collected from 28 patients (25 Klebsiella pneumoniae, seven Escherichia coli, and three Enterobacter cloacae strains). Seven patients were simultaneously colonized with two CTX-R Enterobacteriaceae isolates. CTX-M-15 was detected in most of the CTX-R Enterobacteriaceae isolates (30/35, 88.23%). Three strains co-produced CMY-4 and 22 strains were carbapenem-resistant and co-produced a carbapenemase [OXA-48 (n = 13) or NDM-1 (n = 6)]. Molecular typing of K. pneumoniae strains, revealed eight Pulsed field gel electrophoresis (PFGE) patterns and four sequence types (ST) [ST101, ST147, ST429, and ST336]. However, E. coli isolates were genetically unrelated and belonged to A (n = 2), B1 (n = 2) and B2 (n = 3) phylogenetic groups and to ST131 (two strains), ST572 (two strains), ST615 (one strain) and ST617 (one strain). Five colonized patients were infected by CTX-R Enterobacteriaceae (four with the same strain identified from their rectal swab and one with a different strain). Whether imported or acquired during the stay in the ICU, colonization by CTX-R Enterobacteriaceae is a major risk factor for the occurrence of serious nosocomial infections. Their systematic screening in fecal carriage is mandatory to prevent the spread of these multidrug resistant bacteria.